A 15, 400-year record of environmental magnetic variations in sub-alpine lake sediments from the western Nanling Mountains in South China: Implications for palaeoenvironmental changes. (1st April 2018) - Zhong, Wei; Wei, Zhiqiang; Shang, Shentan; Ye, Susu; Tang, Xiaowen; Zhu, Chan; Xue, Jibin; Ouyang, Jun; Smol, John P.
Graphical abstract: Highlights: This study provides a detail magnetic record of subalpine sediments in the western Nanling Mountains. Magnetic minerals in sediments were mainly originated from surface soils of the catchment. Input of magnetic minerals was closely related to changes in surface runoff. Stabilization of catchment due to vegetation overgrowth plays a role in influencing the input of magnetic minerals. Abstract: A detailed environmental magnetic investigation has been performed on a sub-alpine sedimentary succession deposited over the past 15, 400 years in Daping Swamp in the western Nanling Mountains of South China. Magnetic parameters reveal that fine grains of pseudo-single domain (PSD) magnetite or titanomagnetite are the dominant magnetic minerals in the lake sediments and surface soils collected from the catchment, which suggests that magnetic minerals in lake sediments mainly originated from surface soil erosion of the catchment. Variation of surface runoff caused by rainfall is interpreted as the main process for transportation of weathered soils into the lake. In the Last Deglacial period (LGP, 15, 400–11, 500 cal a BP), the influx of magnetic minerals of detrital material may have been significantly affected by the severe dry and cold conditions of the Last Glacial Maximum. Stabilised conditions of the catchment associated with increased vegetation coverage (e.g., 8000–4500 and 2500–1000 cal a BP) limited the input of magnetic minerals. Intensive soil erosion caused by increased human activity may have given rise to abnormal increases in multiple magnetic parameters after 1000 cal a BP. Because changes in runoff and vegetation coverage are closely related to Asian summer monsoon (ASM) intensity, the sedimentary magnetism of Daping Swamp provides another source of information to investigate the evolution of the ASM.